Relación entre estado nutricional y calidad de la dieta de preescolares atendidos en dos centros de salud de Belén zona baja – 2016 - Koo Pinedo, Priscila (2022)
The present study was carried out in the Villa Belén and 6 de Octubre health centers of the Belén Zona Baja district in 2016, with the aim of collecting data on the quality of the diet and the nutritional status. The Research has a quantitative, non-experimental, descriptive, correlational and transversal approach; we worked with a sample of 307 preschool children; A questionnaire on the frequency of food consumption, and a general data sheet, eating habits, anthropometrics and nutritional status were used as data collection instruments. Reporting results for the nutritional status according to Waterlow that, 64.2% present a normal nutritional status, 15.6% present chronic malnutrition, 6.8% acute malnutrition and 1% present overweight. 12.4% obesity; Regarding the quality of the diet, 68.1% have a poor quality in their diet, 29% regular and 2.9% good quality in the diet. It was also evidenced at a 95% confidence level, through the Chi-Square statistical test, where a level of significance (p-value: 0.000) lower than the proposed significance level (0.05) was found, saying thus, the quality of the diet is related to the nutritional status of our sample sample.